A review of current methods for moisture content measurement - Rotta P. (2019)
This article summarizes our investigation about technologies for moisture sensing, a parameter of analysis and study over many years because it serves to estimate the quality, and performance at commercial and environmental level. This paper presents some contributions. First, we developed a new classification about the most representative system in research and scientific articles. We shows applications of the technology in recent years according to the consulted articles. Also, we expose systems for soil and vegetation moisture measurement, this is an important application in this decade because helps to agriculture and many control applications (forestall fires, earthquakes, etc.). Finally, the tendency about new investigations is presented. This paper is important for microwave sensors designers and investigators in moisture control, because they will have a reference about what kind of method they have to use for a specific application required. © 2019 IEEE.